Assets specificity and financing sources of manufacturing companies (Journal of Academic Finance, 2023)
Purpose: This article aims to analyze the effects of holding specific assets on the choice of financing methods by Cameroonian manufacturing companies.Approach: An exploratory study made it possible to characterize the specific assets of the prospected entities. The verification of research hypotheses required a questionnaire administered to some industrial companies. The data collected was subjected to multiple linear regression analyses.Results: Reputation has a positive and significant impact on capital growth. On the other hand, human capital and R&D have a negative impact on debt financing, unlike outsourcing.Originality: The paper has the originality of examining the specificity of assets in the context of SME. It highlights the reality that assets specificity influence funding sources.
Keywords: Specificity of assets; Private equity; Financial debt; Reputation; Manufacturing Companies